FXR and TGR5 Agonists Ameliorate Liver Injury, Steatosis, and Inflammation After Binge or Prolonged Alcohol Feeding in Mice. Issue 11 (15th October 2018) - Iracheta‐Vellve, Arvin; Calenda, Charles D.; Petrasek, Jan; Ambade, Aditya; Kodys, Karen; Adorini, Luciano; Szabo, Gyongyi
Abstract : Bile acids (BAs) activate various dedicated receptors, including the farnesoid X receptor (FXR) and the Takeda G protein‐coupled receptor 5 (TGR5). The FXR agonist obeticholic acid (OCA) is licensed for the treatment of primary biliary cholangitis and has shown promising results in NASH patients, whereas TGR5 agonists target inflammation and metabolism. We hypothesized that FXR and/or TGR5 agonists may be therapeutic in early alcoholic liver disease (ALD) in mice, in which hepatic inflammation plays a major role. OCA, INT‐777, and INT‐767 are BA derivatives with selective agonist properties for FXR, TGR5, or both, respectively. These compounds were tested in two mouse models (3‐day binge model and prolonged Lieber DeCarli diet for 12 days) of early ALD. Serum alanine aminotransferase and liver histology were used to assess liver injury, Oil Red O staining of liver sections to assess steatosis, and real‐time polymerase chain reaction to assess changes in gene expression. In the ethanol binge model, treatment with OCA and INT‐777 decreased hepatic macrovesicular steatosis and protected from ethanol‐induced liver injury. After prolonged ethanol administration, mice treated with OCA, INT‐767, or INT‐777 showed decreased hepatic steatosis, associated with reduced liver fatty acid synthase protein expression, and protection from liver injury. Treatment with BA receptor agonists in both models of ethanol administration modulated lipogenic gene expression, and decreased liver interleukin‐1β mRNA expression associated with increased ubiquitination of NLRP3 inflammasome through cyclic adenosine monophosphate–induced activation of protein kinase A. Conclusion: OCA, INT‐767, or INT‐777 administration is effective in reducing acute and chronic ethanol‐induced steatosis and inflammation in mice, with varying degrees of efficacy depending on the duration of ethanol administration, indicating that both FXR and TGR5 activation can protect from liver injury in ALD models. Abstract : Bile acids (BAs) activate various dedicated receptors, including Farnesoid X Receptor (FXR), and Takeda G protein‐coupled Receptor 5 (TGR5). The FXR agonist obeticholic acid (OCA) is licenced for the treatment of primary biliary cholangitis and has shown promising results in nonalcoholic steatohepatitis (NASH) patients, while TGR5 agonists target inflammation and metabolism. We hypothesized that FXR and/or TGR5 agonists may be therapeutic in early alcoholic liver disease (ALD) in mice, where hepatic inflammation plays a major role. OCA, INT‐777, and INT‐767 are BA derivatives with selective agonist properties for FXR, TGR5, or both, respectively.